1968
DOI: 10.1039/tf9686402398
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of hydrogen atoms with Fe3+, FeOH2+ and Cu2+ in aqueous solutions

Abstract: The relative rate constants for the reactions of hydrogen atoms with Fe(II), Cu(T1) and methanol, have been obtained over a range of pH. Fe(I1I) reacts entirely as Fe(OH)2+ and there is no measurable contribution from Fe3+ even in 0.2N perchloric acid. The ratio of rate constants are: MeOH : FeOH2+ : CuZf : : 1 : 480 : 38, and kFeOH2 +9500 k ~~3 +.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[ 9 ] The formation of primary species was accounted for by generation values listed in Table S1 (Supporting Information). To account for the interplay between the irradiated aqueous solution products and the Fe‐based species, the reaction network of pure water comprising 83 coupled reactions [ 19 ] was appended by thirteen reactions denoting the interplay with Fe 2+ , Fe 3+ , and [FeOH] 2+ species [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ] (see Table S2 , Supporting Information). The AuRaCh‐compatible reaction set is available at the AuRaCh GitHub repository ( https://github.com/BirkFritsch/Radiolysis‐simulations ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 9 ] The formation of primary species was accounted for by generation values listed in Table S1 (Supporting Information). To account for the interplay between the irradiated aqueous solution products and the Fe‐based species, the reaction network of pure water comprising 83 coupled reactions [ 19 ] was appended by thirteen reactions denoting the interplay with Fe 2+ , Fe 3+ , and [FeOH] 2+ species [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ] (see Table S2 , Supporting Information). The AuRaCh‐compatible reaction set is available at the AuRaCh GitHub repository ( https://github.com/BirkFritsch/Radiolysis‐simulations ).…”
Section: Methodsmentioning
confidence: 99%
“…Reactions (77) and (78) have little impact on the course of the radiolysis in cement media, but may contribute in the capture of a small fraction of the reducing radicals of primary origin in anaerobic environment. The Fe(III) hydride formed in both cases reacts with water (H 3 O + ) and produces dihydrogen [49], as follows: Although radicals H Å and e À aq are very powerful as Fe(III) reducers, the two observed reactions with H Å help to detect a modulation in the reactivity in relation to pH, with the rate constants increasing with the complexation level of Fe(II) [50,51]. As generally observed, the reaction occurs also faster with the base form of antagonistic species [20].…”
Section: Reactions Of Fe(ii) With Oh å and O åàmentioning
confidence: 96%
“…Investigations of the radiolysis of the amino acids glycine and L-alanine in dilute aqueous solution have given evidence that the hydrated electron adds to the carboxyl group.3 Results of the analysis of products of the radiolysis of these systems are consistent with the interpretation that the amino acid anion formed subsequently deaminates to produce a •€ -(R)COOH radical and that this species reacts by abstraction from the parent molecule3 NH,+CH(R)COO-+ CH(R)COOH -XH2C(R)COOH + CH2(R)COOH (1) Electron spin resonance studies of irradiated solid amino acids (usually single crystals) at 77 °K have also shown that electrons formed in the radiolysis add to the carboxyl group and that deamination subsequently occurs upon warming.4"13 These esr studies show that the abstraction step as in reaction 1 does not occur in solid amino acids with alkyl side groups. 6,11,12 No abstraction reaction is found to occur in L-alanine. 6 For valine, deamination is followed by abstraction of a hydrogen atom from the tertiary carbon of the alkyl side group.11,12 Results found for irradiated solid leucine and isoleucine also indicate that abstraction occurs from the tertiary carbon of the alkyl group.11 Results found for solid glycine (R = H) may suggest partial abstraction of one of the a protons;18 however this is uncertain.14…”
Section: Introductionmentioning
confidence: 99%
“…6,11,12 No abstraction reaction is found to occur in L-alanine. 6 For valine, deamination is followed by abstraction of a hydrogen atom from the tertiary carbon of the alkyl side group.11,12 Results found for irradiated solid leucine and isoleucine also indicate that abstraction occurs from the tertiary carbon of the alkyl group.11 Results found for solid glycine (R = H) may suggest partial abstraction of one of the a protons;18 however this is uncertain.14…”
Section: Introductionmentioning
confidence: 99%